Vulnerability of individuals to human trafficking during humanitarian crises - Emelyanovich, Olga V. (Journal of the Belarusian State University. Law, 2025)
This article determines the factors that increase vulnerability of individuals during humanitarian crises (armed conflicts, statelessness, gender stereotypes about the ideal victim, apparent vulnerability). The author produces proposals for measures aimed at reducing vulnerability to human trafficking. It is important to eliminate gender stereotypes of the ideal victim and apparent vulnerability when state bodies take due diligence measures to prevent, investigate the said act, identify victims, provide protection and render assistance to them. When adopting legal, organisational and institutional measures at the domestic level, it is necessary to ensure both proper access to justice for all victims without exception, including persons with disabilities, and guarantee the practical application of the victim’s impunity principle.
Keywords: human trafficking; vulnerability; vulnerable position; victim; humanitarian crisis; gender; stereotypes